DOING THEOLOGY HEURISTICALLY: Methodological Stepping Stones Towards An Intimate Dialogue With The Hindu Religious Other - Kallungal, Martin Sebastian (Asian Horizons, 2012)
Up until the recent past, an empiricist scientific approach had the upper hand in analysing and explaining religious data, and underlying such an approach was an assumption that reality was completely transparent to positivistic rationality. But with developments in hermeneutical studies as well as regional and cultural studies, this confidence in the total sufficiency of positivistic rationality began to waver. In the place of one or another kind of reductionist thinking style, a richer notion of rationality, a rationality that could turn on its own assumptions and procedures, began to emerge, and in the place of closed, discipline-bound scientific practices, many interdisciplinary enterprises emerged that continued to remain rooted in their respective home disciplines while, still sharing the rational resources of one or more other disciplines.